2020
DOI: 10.3389/fimmu.2020.00436
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Analysis of Two Transmembrane C-Type Lectins in Obscure Puffer (Takifugu obscurus)

Abstract: C-type lectins (CTLs) have received widespread attention in animal immune responses. In the present study, two CTLs (ToCTL1 and ToCTL2) were identified from obscure puffer Takifugu obscurus. The open reading frames of ToCTL1 and ToCTL2 were 687 and 1,380 bp, respectively. The predicted ToCTL1 and ToCTL2 proteins contained a single transmembrane region and one typical carbohydrate recognition domain (CRD). Quantitative real-time polymerase chain reaction detected ToCTL1 and ToCTL2 transcripts in all examined ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The levels of expression of two obscure puffer ( Takifugu obscurus) C-type lectins were upregulated in response to infection with A. hydrophila and V. harveyi . The recombinant forms of the lectins showed Ca 2+ -dependent agglutinating activity toward Gram-positive and Gram-negative bacteria, exhibited binding to bacterial peptidoglycan and lipopolysaccharide, and manifested in vitro growth inhibitory activity on four types of bacteria [ 177 ]. Calreticulin with lectin-like and immune activities is a highly conserved protein.…”
Section: Other Biological Activities Of Lectinsmentioning
confidence: 99%
“…The levels of expression of two obscure puffer ( Takifugu obscurus) C-type lectins were upregulated in response to infection with A. hydrophila and V. harveyi . The recombinant forms of the lectins showed Ca 2+ -dependent agglutinating activity toward Gram-positive and Gram-negative bacteria, exhibited binding to bacterial peptidoglycan and lipopolysaccharide, and manifested in vitro growth inhibitory activity on four types of bacteria [ 177 ]. Calreticulin with lectin-like and immune activities is a highly conserved protein.…”
Section: Other Biological Activities Of Lectinsmentioning
confidence: 99%
“…Among marine invertebrates, the sea urchin P. lividus and bivalves belonging to genus Mytilus spp., have been proposed as suitable models to study NP-cellular interactions and immunotoxicity [ 136 , 150 , 151 ], as previously adopted to study other legacy marine pollutants as well as other stressors, including seawater acidification, UV-radiation and microplastics [ 152 , 153 , 154 , 155 ]. Several harmful effects of PS NPs have been reported in mussel hemocytes both in vitro and in vivo, and all of these highlighted the nano-immunomodulation features [ 156 , 157 , 158 ]. Studies performed with short-term primary cultures of coelomocytes exposed to functionalized PS NPs showed that the immune response exerted by sea urchin coelomocytes differed according to PS NP surface charge.…”
Section: Current Knowledge On Enms Marine Ecotoxicitymentioning
confidence: 99%
“…The antimicrobial effects of several CTLs were recently shown for both sweet water [ 71 ] and salt water [ 72 ] fish species. In carp, a number of CTLs were identified to be downregulated on macrophages upon stimulation with the ß-glucan curdlan [ 73 ], which is a well-known ligand of Dectin-1 in mammals [ 74 ].…”
Section: Protective Role Of Veterinary Relevant Ctlsmentioning
confidence: 99%